RANCANG BANGUN SISTEM INFORMASI DATA KEPENDUDUKAN PADA DESA SIWALAN KECAMATAN PANCENG DENGAN BORLAND DELPHI 7.0 - Zainul Abidin Zainul Abidin (Jurnal Fakultas Teknologi Informasi, 2013)
ABSTRACTAbidin, Zainul. 2013. Design of Information Systems Data Population In Siwalan Village District Panceng With Borland Delphi 7. Studies Program, Faculty of Information Technology University of Kanjuruhan Malang Supervisor: Wiwin Kuswinardi, ST., Kom., M.Kom Keywords : Population Data Information System             Computers are one of the technological advances in the development is very helpful in particular government agencies to improve public services in the district head's office Siwalan. Panceng. Population information is one of the major factors in the government in the village because of the demographic information is then able to facilitate and accelerate the population data collection, search for data, and preparing reports are usually membutukan long time it is not efficient. In addition, to avoid errors due to errors that often occur bayaknya population and the similarity of the names. With a population information system is then expected to rule in the village Siwalan can create programs that work well and on target adjusted to the available information. Given the importance of this demographic information is expected in the villages has complete demographic information. The final results of the Population Data System is a data report the population born, people died, people come and people moved on. The population data system for recording mengefesiensi population data, population and determine the number of data menpercepat search is making it easier for users to create reports.